2017
DOI: 10.1016/j.nano.2016.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Improving performance of nanoscale ultrasound contrast agents using N,N-diethylacrylamide stabilization

Abstract: The design of nanoscale yet highly echogenic agents for imaging outside of the vasculature and for ultrasound-mediated drug delivery remains a formidable challenge. We have previously reported on formulation of echogenic perfluoropropane gas nanobubbles stabilized by a lipid-Pluronic surfactant shell. In the current work we describe the development of a new generation of these nanoparticles which consist of perfluoropropane gas stabilized by a surfactant and lipid membrane and a crosslinked network of N, N-die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
70
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 37 publications
5
70
0
Order By: Relevance
“…We also demonstrated that bubbles of >1μm diameter did not extravasate and accumulate, which is also consistent with our prior measurements of microbubbles within the pancreas in models of T1D 11 , as well as being consistent with use of high MW fluorophore dextrans for labelling the vasculature 36,37 . These results are also consistent with prior imaging of NB accumulation within tumors by ultrasound and histology 33,38,39 .…”
Section: Increased Ceus Signal Correlates To Islet Vascular Changessupporting
confidence: 89%
See 1 more Smart Citation
“…We also demonstrated that bubbles of >1μm diameter did not extravasate and accumulate, which is also consistent with our prior measurements of microbubbles within the pancreas in models of T1D 11 , as well as being consistent with use of high MW fluorophore dextrans for labelling the vasculature 36,37 . These results are also consistent with prior imaging of NB accumulation within tumors by ultrasound and histology 33,38,39 .…”
Section: Increased Ceus Signal Correlates To Islet Vascular Changessupporting
confidence: 89%
“…We also utilized a small animal ultrasound machine in these studies using frequencies greater than those clinically applied for pancreas imaging 43,44 . However, nanobubble imaging has been performed using clinically-relevant frequencies, including the detection of increased persistence in certain classes of tumors over other classes 39 . Likewise, higher frequency clinical transducers are also becoming more widely available and utilized especially on the pediatric population.…”
Section: Potential For Translation Of Ceus and Nanobubbles For Clinicmentioning
confidence: 99%
“…10 Compared with other shell materials, nanobubbles with a lipid shell have a good imaging effect and high biocompatibility, and have been widely applied in USMI. [11][12][13][14] However, current studies about USMI of targeted lipid nanobubbles have two challenges: 1) targeted nanobubbles are mainly used for USMI of tumor parenchyma cells from one organ, such as targeted nanobubbles carrying anti-prostate specific membrane antigen aptamer mainly achieve USMI of tumor parenchymal cells in prostate cancer. 15 Although they can achieve intravascular USMI in non-prostatic tumors, USMI of tumor parenchymal cells in non-prostatic tumors cannot be achieved.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to its poor biocompatibility and low LCST, it has seriously affected its future application prospects. Recent studies have shown that the biocompatibility of poly ( N N ‐diethylacrylamide) (PDEA) is far superior to that of PNIPAM, and its LCST is also higher than that of PNIPAM. If thermo‐sensitive block copolymer with suitable LCST could be used as carrier to the immobilization of PGA, the carrier would realize the aim that the immobilization and catalyzation would be conducted at solution state, while the recovery would be carried out under its gelatin state.…”
Section: Introductionmentioning
confidence: 99%